The effectiveness of private label brand strategies in FMCG - Balidis, Dimitri (My University, 2015)
ABSTRACT In a background of extreme resource constraints, South African public health care institutions are increasingly faced with taxing trials in their quest to maintain effective service delivery. This study focuses on determining the levels of public service motivation of nurses working in this arena, and aims to determine the potential of organisational factors in the form of red tape, and the cultural archetypes of rational, hierarchical, group, and developmental cultures, to serve as antecedents of public service motivation. There has been a vast expanse of work performed in the area of public service motivation, its antecedents and its outcomes. The major focus when assessing antecedents of public service motivation centred on intrinsic causes. The search for extrinsic causes of public service motivation is gaining traction. The notion that organisational factors act as antecedents of public service motivation is an intriguing concept that been shown to display some influence. A quantitative departmental study of a random sample of 207 nurses in the Chris Hani Baragwanath hospital across all nursing levels, within varying departments, was conducted utilising paper based questionnaires, where the levels of public service motivation and its constituent factors, the cultural archetypes, and red tape were measured, using validated rating instruments. The internal validity of the factor structure of the major constructs were analysed with confirmatory factor analysis. In addition, the relationship between public service motivation and the organisational factors were assessed using multiple regressions and moderation. The study reveals high levels of each of the four factors of public service motivation, with self-sacrifice scoring the lowest. Each of the factors display slight variation within the various subgroups of nurses, alluding to the fact that they function as unique factors within the PSM construct. The organisational factors prove to have influence as antecedents of PSM. Each of the cultural archetypes have unique interactions with the PSM factors, with group culture having the greatest impact. Red tape has a minimal influence on PSM and the propensity for hierarchical culture proves to be a contributing factor. These findings suggest that individuals self-select for positions in public health due to intrinsic motives, and that organisation-specific factors serve as extrinsic motives that either hinder, maintain or enhance this motivation. An enhanced comprehension of how management systems influence public service motivation, will provide a powerful tool to harness employee public service motivation and consequently strengthen employee commitment and loyalty beyond the capability of monetary incentives.
MBA 2015
Keywords: Brand name products,House brands ,Pricing ,Consumer goods